2013
DOI: 10.1097/jto.0b013e318292c500
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate Synthase Expression and Outcome of Patients Receiving Pemetrexed for Advanced Nonsquamous Non–Small-Cell Lung Cancer in a Prospective Blinded Assessment Phase II Clinical Trial

Abstract: The primary endpoint was met; low TS expression was associated with longer PFS. Further randomized studies are needed to explore nuclear TS IHC expression as a potential biomarker of clinical outcomes for pemetrexed treatment in larger patient cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 27 publications
(40 reference statements)
2
58
0
1
Order By: Relevance
“…Multiple studies have demonstrated an association between TYMS expression levels and pemetrexed response (37)(38)(39). In these studies, NSCLC tumors and cells with lower expression of TYMS demonstrated enhanced response to pemetrexed.…”
Section: Kras Status Predictsmentioning
confidence: 85%
“…Multiple studies have demonstrated an association between TYMS expression levels and pemetrexed response (37)(38)(39). In these studies, NSCLC tumors and cells with lower expression of TYMS demonstrated enhanced response to pemetrexed.…”
Section: Kras Status Predictsmentioning
confidence: 85%
“…Several candidate predictive biomarkers including expression of thymidylate synthase, miR-25, miR-145, miR-210 and serum leptin have been studied but not sufficiently validated for the routine clinical use. [18][19][20][21] In this study, we focused on the association between TTF-1 expression and the efficacy of pemetrexed-based chemotherapy in patients with advancedstage non-squamous NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2280 patients analyzed with TS protein expression were included in the meta-analysis. Eighteen studies were performed in Asia [7,14,18-20, 23,29-39], 4 in Europe [17,21,40,41] and 2 in America [16,42]. OS or PFS were compared according to tumor TS protein expression levels (high/low or positive/negative) (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%